Longitudinal Associations of Self-Reported Visual, Hearing, and Dual Sensory Difficulties With Symptoms of Depression Among Older Adults in the United States - Killeen, Olivia J.; Xiang, Xiaoling; Powell, Danielle; Reed, Nicholas S.; Deal, Jennifer A.; Swenor, Bonnielin K.; Ehrlich, Joshua R. (Frontiers in Neuroscience, 2022)
Evidence conflicts on the association between sensory difficulty and depression. Few studies have examined this association using longitudinal or population-based data. We used data from Rounds 1-9 of the nationally-representative National Health and Aging Trends Study to evaluate the longitudinal association between self-reported visual, hearing, and dual sensory difficulties and clinically significant depressive symptoms. Multivariable Cox regression models were used to evaluate the hazard of incident depressive symptoms. Group-based trajectory modeling identified depressive symptom trajectories (DSTs). Multinomial logistic regression was used to examine the association between sensory status and DSTs. 7593 participants were included. 56.5% were female. 53.0% were 65-74 years old. 19.0% (95% CI 17.9-20.2%) had hearing, 5.6% (4.9-6.4%) had visual, and 3.3% (2.9-3.8%) had dual-sensory difficulties at baseline. Hazard ratios for depressive symptoms in those with visual, hearing, and dual-sensory difficulties were 1.25 (95% CI 1.00-1.56, p=0.047), 0.98 (95% CI 0.82-1.18, p=0.82), and 1.67 (95% CI 1.29-2.16, p<0.001), respectively, relative to those without sensory difficulty. A model with four trajectory groups best fit the data. Group 1 (35.8% of the sample, 95% CI: 34.1-37.4) had persistently low risk of depressive symptoms; Group 2 (44.8%, 43.4-46.3) had low but increasing risk; Group 3 (7.1%, 6.2-8.3) had moderate risk; and Group 4 (12.4%, 11.5-13.3) had moderate to high risk that increased. Compared to those without sensory difficulties, individuals with each difficulty were significantly more likely to belong to a group other than Group 1. This study reveals associations between sensory difficulties and mental health that can inform public health interventions.